A Pilot Study Approach to Assessing the Reliability and Validity of Relevancy and Efficacy Survey Scale - Khanal, Bishnu; Chhetri, Deb Bahadur (Janabhawana Research Journal, 2024)
This paper is based on the pilot study that aims to assess the reliability and validity of the attitude measurement scale towards the relevance of mathematical knowledge of real analysis for secondary-level mathematics instruction. Research tool validation and reliability estimation are challenging due to the complexity of its procedure. This study establishes procedural guidance for piloting and tool validation. The survey method was used to conduct the pilot study. Thirty participants filled in the 45 indicators of relevance measurement and 10 mathematical efficacy measurement indicators. The reliability was assessed with Cronbach’s Alpha formula while the validity of the questionnaire was examined through item-total correlation with each item by using Pearson’s formula. The content validity index was also calculated based on the expert judgment method. The reliability indicator was found to be more than 0.70 and the validity indicator falls in the acceptable range. Therefore, developed scale is valid and reliable to measure the teachers’ attitudes on the relevancy of mathematical knowledge of real analysis of school’s mathematics instruction based on pilot study results. Furthermore, this study guides the pilot study procedure for survey research and especially benefits those looking to validate their Likert-type survey scale in any research.